Three new yeast species from flowers of Camellia sinensis var. assamica collected in Northern Thailand and their tannin tolerance characterization - Kanpiengjai, Apinun; Kodchasee, Pratthana; Unban, Kridsada; Kumla, Jaturong; Lumyong, Saisamorn; Khunnamwong, Pannida; Sarkar, Dipayan; Shetty, Kalidas; Khanongnuch, Chartchai (Frontiers in Microbiology, 2023)
Our recent research study focused on Miang fermentation revealed that tannin-tolerant yeasts and bacteria play vital roles in the Miang production process. A high proportion of yeast species are associated with plants, insects or both and nectar is one of the unexplored sources of yeast biodiversity. Therefore, the aims of this study were to isolate and identify yeasts of tea flowers of Camellia sinensis var. assamica, and to investigate their tannin-tolerance which is a property essential to Miang production processes. Eighty-two yeasts were recovered from a total of 53 flower samples in northern Thailand. It was found that two and eight yeast strains were distinct from all other known species within the genera Metschnikowia and Wickerhamiella, respectively. These yeast strains were described as three new species, namely Metschnikowia lannaensis, Wickerhamiella camelliae, and W. thailandensis. The identification of these species was based on phenotypic (morphological, biochemical, and physiological characteristics) and phylogenetic analyses of a combination of the internal transcribed spacer (ITS) regions and the D1/D2 domains of the large subunit (LSU) ribosomal rRNA gene. The yeast diversity in tea flowers acquired from Chiang Mai, Lampang, and Nan provinces had positive correlation with those acquired from Phayao, Chiang Rai, and Phrae, respectively. W. azyma, Candida leandrae, and W. thailandensis were the species uniquely found in tea flowers collected from Nan and Phrae, Chiang Mai, and Lampang provinces, respectively. Some of the tannin-tolerant and/or tannase producing yeasts were associated with yeasts in commercial Miang process and those found during Miang production i.e., C. tropicalis, Hyphopichia burtonii, Meyerozyma caribbica, Pichia manshurica, C. orthopsilosis, Cyberlindnera fabianii, Hanseniaspora uvarum, and Wickerhamomyces anomalus. In conclusion, these studies suggest that floral nectar could support the formation of yeast communities that are beneficial for Miang production.